Communication training program for nurses caring for patients with aphasia: a quasi-experimental study - Yujin Hur; Younhee Kang (BMC Nursing)
Abstract Background Nurses are key communication partners for patients with aphasia. Nurses’ skills are vital for improving the patients’ environment and nursing performance. This study develops and evaluates the effectiveness of a communication training program for nurses who care for patients with aphasia. Methods A program was developed based on the Intervention Mapping Protocol. Then, a simulation using a standardized patient with aphasia and surveys were conducted. Program effectiveness was evaluated using a quasi-experimental framework with a non-equivalent control group and pretest-posttest non-synchronized design. Results The two groups exhibited statistical significant differences in health communication competence, knowledge of aphasia, patient advocacy, clinical decision-making, and compassionate competence. Conclusion This study developed communication training for nurses who care for patients with aphasia. The effectiveness test showed that this training affected nurses’ knowledge, attitude, and skills. Clearly, communication education for nurses is important to provide comprehensive care for patients with aphasia and can enhance nursing.